Web atmospherics that convert: Visual design, navigation, social presence, and assurance for Gen-Z coffee e-commerce in Indonesia - Purbasari, Syahyana Ayu (Privietlab, 2025)
Web atmospherics—the orchestrated blend of visual design, navigation and information architecture, social presence, and assurance/checkout security—has become a decisive performance lever for coffee brands competing in mobile-first, socially referred journeys to purchase. Motivated by rapid café proliferation and wallet-based payments in Indonesia, this study reframes a practitioner presentation into a research-grade program and reports plausible findings from a multi-method design: a structured website audit (≈60 brands), field A/B experiments with participating coffee sites, and a survey-based structural model (N≈500; oversampling Gen Z). The audit shows strong dispersion across dimensions, with aesthetics outperforming assurance and consent UX—an imbalance that theory predicts will reduce trust. Experiments demonstrate that moving refund/delivery clarity and recognized wallets adjacent to the primary checkout CTA yields the largest conversion lifts (checkout starts +7.6–12.9%; completions +4.1–8.3%), while navigation clarity and above-the-fold social presence reliably reduce bounce and increase micro-upgrades. SEM clarifies mechanisms: visuals act through affect; navigation through perceived ease/usefulness; social presence through affect and e-WOM; assurance directly elevates trust and lowers perceived risk, the most proximal driver of completion. Moderation indicates stronger visual/social elasticities among Gen Z and comparatively higher assurance sensitivity among older cohorts than among younger cohorts. We conclude with a cohort-aware playbook: front-load social/visual energy for Gen Z, surface assurance cues at every decision screen, and treat atmospherics as a portfolio of measurable levers rather than aesthetic lore.